An exposomics analysis of 125 biomarkers of exposure to food contaminants and biomarkers of oxidative stress: a randomized cross-over chrononutrition trial of healthy adults - Hayley Kunde; Elina I. Ioannou; Jasmin Chovatiya; Ravikumar Jagani; Pantelis Charisiadis; Manish Arora; Syam S. Andra; Konstantinos C. Makris (Environment International, 2025)
Background: Contaminants in food counteract the beneficial effects of nutrients by interfering with their absorption/distribution/metabolism/excretion characteristics and implicated in chronic disease pathogenesis. The CIRCA CHEM chrononutrition trial was used to expand and replicate its earlier results from two biomarkers of exposure to pesticides to 125 biomarkers of exposure to food contaminants/xenobiotics, using exposomics. Objectives: We determined i) the effect of time restricted eating (TRE) consumption of fruits and vegetables either in light or dark phases of the 24-h period (five-a-day portions for 14 days), within ad libitum diet on 125 biomarkers of exposure to food-associated contaminants in healthy adults, ii) the chrono-metabolism patterns in biomarker concentrations across/within treatment phases (light vs dark); and iii) the contaminants associated with oxidative stress, including 4-hydroxy-2-nonenal mercapturic acid (HNEMA) and 8-iso prostaglandin F2α (F2A8IP). Methods: We characterized the temporal patterns of the TRE treatment effectiveness on biomarkers of exposure using an exposome-wide association study (ExWAS) approach, by applying linear mixed-effects models (LME) to evaluate treatment phase effects and interactions of treatment x time. Associations between contaminants and oxidative stress were further explored using LASSO regression, followed by additional LME, while adjusting for sociodemographics, body mass index and cortisol. Results: A wide within-subject concentration variability for most biomarkers of exposure to food contaminants/xenobiotics was observed. The ExWAS approach confirmed that TRE significantly influenced the concentration and temporal patterns of multiple food contaminants/xenobiotics, including pesticides, smoking, volatile organics, phytoestrogens, parabens, and flame retardants, demonstrating their chrono-differentiated metabolism, depending on the timing of fruit and vegetable consumption within the 24-h period. Some of them (pesticides and VOCs) exhibited significant associations with lipid oxidative stress. Discussion: Understanding how the circadian rhythm interacts with metabolic systems to influence the metabolism of both nutrients/bioactives and food contaminants would be of high importance in the era of precision health and precision nutrition.